Cow Urine Mediated Green Synthesis of Nanomaterial and Their Applications: A State-of-the-art Review - Harshal Dabhane; Suresh Ghotekar; Pawanwan Tambade; Shreyas Pansambal; H C Ananda Murthy; Rajeshwari Oza; Vijay Medhane (Journal of Water and Environmental Nanotechnology, 2021)
Nowadays, green syntheses have received crucial attention as a reliable, developing and eco-benevolent protocol for synthesizing a broad range of nanomaterials (NMs) including metal/metal oxides NMs, bio-inspired materials and hybrid/composite NMs. As such, biogenic synthesis is regarded as a significant tool to mitigate the destructive impacts associated with the conventional approaches of synthesis for NMs generally utilized in industry and laboratory. In this review, we summed up the general protocols and mechanisms of green synthesis routes, especially for silver (Ag), silver oxide (Ag2O), cadmium (Cd), copper (Cu), copper ferrite (CuFe2O4), palladium (Pd), aceprophyline, cellulose and graphene nanomaterials/nanoparticles using cow urine. Importantly, we explored the main role of biological constituents which is existed in cow urine. These essential biomolecules act as reducing/stabilizing agents in solvent systems. The stability, phase formation and surface morphology of NMs using characterization techniques are also discussed. Finally, we covered the eclectic applications of such synthesized NMs in terms of anti-asthma, antimicrobial, antituberculosis, antioxidant, anticancer activity, catalytic activity and removal of pollutants dyes.